SPECTRUMS OF SUPERCONDUCTING STATES AND TRIPLET EFFECTS IN SUPERCONDUCTOR/FERROMAGNET MULTILAYERS - V. N. Kushnir (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
We report the results of studies of triplet superconductivity in structures with alternating superconductor and ferromagnet layers, as a part of the general problem of the properties of the spectra of superconductivity states depending on the magnetic state of the multilayer structure. Ferromagnetic layers are assumed monodomain and possessing inplane magnetic moments. In numerical examples, we used the parameters of the well-studied Nb/PdNi system. The critical temperatures and distributions of singlet and triplet currents depending on the relative orientation of the magnetic moments of the ferromagnetic layers are calculated in the formalism of the Usadel equations for 5- and 3-layer irregular structures. The following results are obtained. (1) The channeling effect of triplet pairs by a narrow central layer of a superconductor with complete suppression of the singlet component in it was confirmed. (2) The “0–1”-transition between the phases of a superconducting condensate of opposite symmetry induced by the transport current is predicted. (3) The effect of a double crossover of states on the dependence of the critical temperature, Tc, versus the angle θ between the magnetic moments of the ferromagnetic layers adjacent to the central layer of the superconductor in a 3-layer structure is predicted. The crossovers are reflected by a sharp turns in the Tc (θ) curve, while the infinitely small asymmetry of the structure eliminates the non-analyticity of this characteristic.